Living with Google: Perspective on Humanities Computing and Digital Libraries. - Hockey, Susan (Literary & Linguistic Computing, 2005)
Presents the text of speech of Susan Hockey during the joint conference of the 2004 Association of Literary and Linguistic Computing/Association of Computers in the Humanities in Gothenburg, Sweden.